تلقي النص الشعري الجاهلي لدى مصطفى ناصف من خلال كتابه :قراءة ثانية لشعرنا القديم - معــرف, رضـا (قــــــراءات; No 10 (2017): مجلة قراءات, 2019)
حظي الشعر الجاهلي بعناية خاصة من قبل النقاد، الذين طالما مثلت لهم نصوصه التحدي الأعظم، فقد كان هذا الشعر على الدوام موضع دراسة وفحص واستنطاق وإعادة تقويم، ضمن ما ينطوي عليه الفعل النقدي من مهمات متنوعة كالتحليل والاستقراء والتأويل والتلقي، والإعجاب، والإدراك، والاستجابة. ومصطفى ناصف من أولئك النقاد الذين اهتموا بالنص الشعري الجاهلي من خلال كتابه : قراءة ثانية لشعرنا القديم، محاولا في فصوله الثمانية اقتحام عالم القصيدة المغلق العسير، كاشفا عن روائعه غير المعلومة. فكيف يا ترى كان التلاقح بين النص والمبضع النقدي، وبأي منهج تم التشريح؟ Abstract : Receive the Pre-Islamic era poetic texte for Mustafa Nasif through his book: A second reading of our old poetry Pre-Islamic poetry had a special attention by critics, whose texts have always represented the greatest challenge. This poetry has always been the subject of study, examination, questioning and re-evaluation, including the critical act of various tasks such as analysis, extrapolation, interpretation, reception, admiration, cognition and response. And Mustafa Nasif of those critics who were interested in the Pre-Islamic text through his book: a second reading of our old poetry, trying in the eight chapters to break into the world of the poem closed hard, revealing his unknown masterpieces . How, then, was the reconciliation between the text and the critical, and in what approach was the autopsy?